Studies on the Biosorption of Textile Dyes from Aqueous Solutions Using (L.) Leaf Sheath Fibres - Mohamed Chaker Ncibi; Borhane Mahjoub; Mongi Seffen (Adsorption Science & Technology)
The adsorption of two textile dyes onto a low-cost and unexploited marine biomass, Posidonia oceanica (L.), was investigated in batch mode. The biosorption process was studied as a function of contact time, initial pH and temperature. The highest dye adsorption capacities attained at 30°C were 3.081 mg/g at pH 2 for the Direct dye and 4.252 mg/g at pH 5 for the Reactive dye. The Freundlich, Langmuir and Redlich–Peterson adsorption models were used to determine the parameters of the equilibrium data and, under the operating conditions studied, the best fit to the experimental curves was obtained using the Freundlich model. The thermodynamic constants of the adsorption process (i.e. ΔG 0 , ΔH 0 and ΔS 9 ) were evaluated as −6.36 kJ/mol, 57.80 kJ/mol and −103.45 J/(mol K), respectively, for the Direct dye and as −3.22 kJ/mol, 84.10 kJ/mol and −225.55 J/(mol K), respectively, for the Reactive dye. Consequently, the adsorption of dyes onto P. oceanica biomass was favourable, endothermic and spontaneous.